Generation of robust entangled states in a non-hermitian periodically driven two-band Bose-Hubbard system - Parra Murillo, Carlos Alberto; Wimberger, Sandro (Physical review, 2017)
A many-body Wannier-Stark system coupled to an effective reservoir is studied within a non-Hermitian approach in the presence of a periodic driving. We show how the interplay of dissipation and driving dynamically induces a subspace of states which are very robust against dissipation. We numerically probe the structure of these asymptotic states and their robustness to imperfections in the initial-state preparation and to the size of the system. Moreover, the asymptotic states are found to be strongly entangled making them interesting for further applications.